(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The study aims to evaluate the workshop safety management skills among mechanical engineering students in Edo State, Nigeria. With the increasing complexity of engineering tasks and the inherent risks associated with workshop environments, it is crucial to ensure that students are well-equipped with the necessary safety skills. This research employs a mixed-method approach, combining quantitative surveys and qualitative interviews to gather comprehensive data on students’ safety practices, awareness, and compliance with established safety protocols. A sample of 200 mechanical engineering students from three major institutions in Edo State participated in the study. The survey assessed various dimensions of workshop safety, including the use of personal protective equipment (PPE), adherence to safety guidelines, emergency response preparedness, and the effectiveness of safety training programmes. Additionally, in-depth interviews with selected students and workshop supervisors provided insights into the challenges and barriers to effective safety management. Preliminary findings indicate a moderate level of compliance with safety protocols, with significant variations across different institutions. While most students demonstrated basic knowledge of safety practices, gaps were identified in the consistent use of PPE and emergency response procedures. The study highlights the need for enhanced safety training programmes and the integration of practical safety management modules into the engineering curriculum. The research underscores the importance of fostering a safety-conscious culture within engineering workshops to mitigate risks and ensure the well-being of students. Recommendations include regular safety audits, continuous professional development for instructors, and the incorporation of advanced safety technologies in workshop settings.